PERAN GURU BIMBINGAN KONSELING TERHADAP MINAT MELANJUTKAN PENDIDIKAN BAGI SISWA MAS YPP JAMANIS - Maulana, Acep Ridwan; Yunita, Rika; Sutansyah, Lexy; Agustini, Aini Ali (Journal Education and Government Wiyata, 2024)
Guidance and Counseling (G&C) is a process of interaction between a counselor and a counselee, either directly or indirectly, aimed at assisting the counselee in developing their potential and solving the issues they are facing. This process involves systematic, objective, logical, and programmed efforts by the counselor to facilitate the development of independence in the counselee's life. The understanding of G&C encompasses face-to-face activities conducted by counseling experts, either individually or in groups, providing additional knowledge. The main objective of G&C is to aid the counselee in self-understanding, potential development, and issue resolution. Counseling is defined as a personal relationship conducted face-to-face between a counselor and a counselee, involving the development of specific counselor skills to provide a learning environment. This research adopts a qualitative approach, wherein the researcher examines informants as subjects in their daily environment. This method is chosen to obtain more comprehensive, in-depth, credible, and meaningful data. Data analysis involves stages of data reduction, data presentation, and drawing conclusions and data verification. The research findings indicate an increased interest among students of MAS YPP Jamanis in pursuing higher education, albeit within relatively low figures. Factors such as technological advancements and students' enthusiasm in creating LTMPT (National University Entrance Test) accounts contribute to this interest. Guidance counselors play a role in providing guidance and understanding to students about the university world, as well as helping channel their interests and talents. Challenges faced by guidance counselors involve differences in perception between students and their parents, requiring effective solutions. Strategies to increase student interest include educational motivation seminars and campus organization involvement. The research concludes that the Guidance and Counseling at MAS YPP Jamanis can be considered effective, with aspects of planning, organization, implementation, and supervision evaluated as good to excellent.